Effects of increasing lysine:calorie ratio in pigs grown in a commercial finishing environment - R G Main; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
Seven experiments using 7,801 pigs (75 to 265 lb) were conducted to determine the biologic and economic effects of increasing dietary lysine in commercially reared grow-finish pigs. Each study was generally 28 d long and evaluated a different weight range of the grow-finish period for barrows (3 trials) and gilts (4 trials), respectively. All studies contained six dietary treatments of incrementally increasing lysine:calorie ratio. The primary response criteria measured were growth, carcass, and economic performance. Pigs fed high-energy diets in early finishing (<150 lb) have only moderate biological responses to a wide range of dietary lysine. However, increasing dietary lysine levels in late finishing (>150 lb) has more quantitatively significant effects on growth and carcass performance. Due the magnitude of the biological responses observed, economic penalties for feeding below the lysine requirement were modest early and severe later in the grow-finish period. These studies indicate that income over marginal feed cost (IOMFC) is consistently optimized near the biological requirement for optimal growth and feed conversion. However, feed cost per pound of gain is consistently minimized below these biological requirements. Therefore, diet costs alone provide little value in developing cost effective feeding strategies. In addition, prediction equations to calculate the optimum lysine:calorie ratio based on body weight (BW, lb) were developed. The lysine:calorie ratio prediction equation is: lysine:calorie ratio, g total lysine/ Mcal ME = -.006045 × BW + 3.694 for barrows and lysine:calorie ratio = -.00744 × BW + 4.004 for gilts.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Lysine; Swine; Calorie ratio